2008
DOI: 10.1111/j.1532-5415.2008.01863.x
|View full text |Cite
|
Sign up to set email alerts
|

A Senior Center–Based Pilot Trial of the Effect of Lifestyle Intervention on Blood Pressure in Minority Elderly People with Hypertension

Abstract: This senior center-based lifestyle intervention was associated with a significant reduction in SBP and adherence to prescribed antihypertensive medications and diet in the intervention group. Participant retention and group attendance rates suggest that implementing a group-counseling intervention in senior centers is feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 14 publications
0
32
0
Order By: Relevance
“…However, few studies have implemented a multidimensional intervention that is tailored to patients' needs [3,24]. In particular, there is little evidence to support the benefits of intervention in community-based settings such as senior center [4,25]. The HAHA program in our study integrated the education for behavior modification into exercise intervention.…”
Section: Discussionmentioning
confidence: 95%
“…However, few studies have implemented a multidimensional intervention that is tailored to patients' needs [3,24]. In particular, there is little evidence to support the benefits of intervention in community-based settings such as senior center [4,25]. The HAHA program in our study integrated the education for behavior modification into exercise intervention.…”
Section: Discussionmentioning
confidence: 95%
“…When the TS was subdivided into NT and HT groups, greater reductions in BP during the first hour post-exercise were observed in the HT group than in the NT group, although the reduction was still significant in the latter group. Many investigators 6,[22][23][24] have observed post-exercise reductions in BP only in hypertensive persons, regardless of age. The results reported by these investigators have suggested that acute physical exercise does not promote BP reductions in NT individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The beneficial effect of aerobic physical activity on CV risk factors has been reported even in the elderly. [2][3][4][5][6] Cross-sectional studies have shown that physical activity is associated with lower values of pulse wave velocity carotid-femoral (PWVcf), a surrogate marker of subclinical vascular damage. [7][8][9] To date, only a few studies have evaluated the effect of physical activity on PWVcf in the elderly.…”
mentioning
confidence: 99%